ANALISIS STRATEGI PENINGKATAN PAJAK HOTEL, RESTORAN DAN RUMAH MAKAN DALAM MENUNJANG PENDAPATAN ASLI DAERAH DI KOTA KENDARI - Syaifudin Suhri Kasim; Juhaepa Juhaepa; Masrul Masrul; Suharty Roslan; Megawati A. Tawulo (Universitas Halu Oleo, 2022)
This study aims to analyze the strategy of increasing hotel, restaurant, and restaurant tax revenue in Kendari City in supporting locally-generated revenue. This type of research is an associative survey research with a qualitative descriptive approach. The population in this study are a hotel, restaurant, and restaurant entrepreneurs plus officials from the Regional Revenue Agency. Samples were taken using a purposive technique. Data were collected using questionnaires, interviews, and observations of all respondents and informants. Data were analyzed descriptively and SWOT analysis. The results showed that the strategy used in increasing hotel, restaurant, and restaurant taxes to support Kendari City's locally-generated revenue was through structuring tax management mechanisms and procedures, developing institutional capacity, and through tax development policies. Then combine the various strengths and weaknesses of the organization by taking advantage of opportunities as carefully as possible and while dealing with the challenges faced by the organization in an effort to increase Regional Original Income